EVALUATION OF GENETIC DIVERSITY OF SANDALWOOD (SANTALUM ALBUM, L.) IN ACEH, INDONESIA AND IT'S ESSENTIAL OIL CHARACTERISTICS: Evaluasi keragaman genetik cendana di Aceh, Indonesia dan karakteristik minyaknya - Nurochman, Deden; Matangaran, Juang Rata; Santosa, Gunawan; Suharjito, Didik; Sari, Rita Kartika (Malaysian Journal of Science, 2019)
Intensive utilization of sandalwood in Aceh has raised concern over the potential impact on quantity and quality of sandalwood. This practice in the long run is suggested can lead to a decrease of its genetic resources. This study is aimed at analyzing the genetic diversity of sandalwood populations in their natural habitat in Aceh, assessing the genetic affinity with sandalwood in East Nusa Tenggara (NTT), and evaluating the essential oils characteristics. We propose that this study contributes to provide an information on responsible utilization policy of sandalwood in the future. We collected leaf samples from 5 populations across Indonesia where 4 sites are located in Aceh and 1 site in NTT. In Aceh, samples were collected from Kuta Malaka, Suka Makmur, Padang Tiji and Muara Tiga while in NTT from Maulafa. The evaluation of sandalwood genetic diversity was conducted using RAPD method with UPGMA and NTSYS version 2.0 programs. Sandalwood essential oil was extracted from sandalwood trees (stems and roots) from 4 different diameter classes using water and steam distillation method was applied for 8 hours. The oil characteristic evaluation was measured based on the concentration of santalol compounds using GC-MS method and the specific gravity. The results showed that the Suka Makmur population had the highest genetic diversity, thus it has the potential to be developed as the center of sandalwood diversity in Aceh. Sandalwood populations in Aceh have genetic affinity with sandalwood populations in NTT with a level of genetic diversity of 16%. This shows that sandalwood populations in Aceh is likely originated from NTT. Characteristics of the essential oil which met the quality standards (ISO) derived from the tree diameter â‰¥ 15 cm with the proportions of heartwood were 48.53% on stems and 52.36% on roots. Therefore, we propose that selection of sandalwood tree diameter can contribute to sandalwood utilization strategy for maintaining sandalwood quantity and quality